TRAF6-deficient mice display hypohidrotic ectodermal dysplasia - Naito, Asuka (National Academy of Sciences, 2002)
Tumor necrosis factor receptor (TNFR)-associated factor 6 (TRAF6) is an adapter protein that links signals from members of the TNFR superfamily and Toll/IL-1 receptor family to activation of transcription factors NFκB and AP-1. Analysis of TRAF6-deficient mice revealed that TRAF6 is essential for normal bone formation and establishment of immune and inflammatory systems. Here we report that TRAF6 deficiency results in defective development of epidermal appendixes, including guard hair follicles, sweat glands, sebaceous glands of back skin, and modified sebaceous glands such as meibomian glands, anal glands, and preputial glands. Except the sebaceous gland impairment, these abnormal phenotypes are identical to those observed in Tabby (Ta), downless (dl), and crinkled (cr) mice, which are models of hypohidrotic (anhidrotic) ectodermal dysplasia in human. β-catenin and mucosal addressin cell adhesion molecule-1, an early marker of developing guard-hair follicles is absent in the skin of TRAF6-deficient embryos. Thus, TRAF6 is essential for development of epidermal appendixes. TRAF6 does not associate with the cytoplasmic tail of the dl protein (DL)/ectodysplasin receptor (EDAR) receptor, which, when mutated, results in hypohidrotic (anhidrotic) ectodermal dysplasia. However, TRAF6 associates with X-linked ectodysplasin-A2 receptor (XEDAR) and TNFR super family expressed on the mouse embryo (TROY/toxicity and JNK inducer (TAJ), which are EDAR-related members of the TNFR superfamily that are expressed at high level in epidermal appendixes. Furthermore, TRAF6 is essential for the XEDAR-mediated NFκB activation. Our results suggest that TRAF6 may transduce signals emanating from XEDAR or TROY/TAJ that are associated with development of epidermal appendixes.